Micro-Grid Oil Palm Plantation Waste Gasification Power Plant in Indonesia: Techno-Economic and Socio-Environmental Analysis - Jaka Isgiyarta; Bambang Sudarmanta; Jalu Aji Prakoso; Eka Nur Jannah; Arif Rahman Saleh (Energies, 2022)
The utilization of new and renewable energy sources explicitly based on biomass needs to be increased to reduce dependence on fossil fuels. One of the potential biomasses of plantation waste in Indonesia that can be utilized is oil palm plantation waste in the form of fronds and trunks that are converted with multi-stage downdraft gasification technology. This study aimed to conduct a technical analysis, economic analysis, investment risk analysis, social analysis, and an environmental impact assessment of power plants fueled by oil palm plantation waste. The method used was the upscaling of a prototype of a 10 kW power plant to 100 kW. The results showed that it was technically and economically feasible to apply. The economic indicators were a positive NPV of USD 48.846 with an IRR of 9.72% and a B/C ratio of 1.16. The risk analysis predicted a probability of an NPV 49.94% above the base case. The study of the social aspects suggested that the construction of power plants has a positive impact in the form of increased community income and the growth of new economic sectors that utilize electricity as a primary source. An analysis of the environmental effects is critical so that the impacts can be minimized. Overall, the construction of small-scale power plants in oil palm plantations is worth considering as long as it is carried out following the applicable regulations.